Coeliac disease and the liver: spectrum of liver histology, serology and treatment response at a tertiary referral centre. Issue 5 (29th September 2017) - Majumdar, Kaushik; Sakhuja, Puja; Puri, Amarender Singh; Gaur, Kavita; Haider, Aiman; Gondal, Ranjana
Abstract : Background: Coeliac disease (CD) is a gluten-sensitive enteropathy diagnosed on the basis of ESPGHAN criteria and clinical response to gluten-free diet (GFD). Histological abnormalities on liver biopsy have been noted in CD but have seldom been described. Aims: To assess the histological spectrum of 'coeliac hepatitis' and possibility of reversal of such features after a GFD. Methods: Twenty-five patients with concomitant CD and hepatic derangement were analysed for clinical profile, laboratory investigations and duodenal and liver biopsy. A histological comparison of pre- and post-GFD duodenal and liver biopsies was carried out, wherever possible. Results: Fifteen patients presenting with CD subsequently developed abnormal liver function tests; 10 patients presenting with liver disease were found to have tissue positive transglutaminase in 70% and antigliadin antibodies in 60%. Serological markers for autoimmune liver disease (AILD) were positive in eight patients. Liver histology ranged from mild reactive hepatitis, chronic hepatitis, steatosis to cirrhosis. Liver biopsies after a GFD were available in six cases, of which five showed a decrease in steatosis, portal and lobular inflammation and fibrosis score. Conclusion: Coeliac hepatitis could be a distinct entity and the patients may present with either CD or secondary hepatic derangement. Evaluation for the presence of CD is recommended for patients presenting with AILD, unexplained transaminasaemia or anaemia. This is one of the very few studies demonstrating the continuum of liver histological changes in 'coeliac hepatitis'. Trial of a GFD may result in clinicopathological improvement of 'coeliac hepatitis'.